2009
DOI: 10.1007/s00420-009-0487-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to poultry dust and health effects in poultry workers: impact of mould and mite allergens

Abstract: Hazardous levels of Der p 1, endotoxin and moulds were determined in poultry houses. High prevalence of work-related symptoms and IgG antibodies to moulds was found in PW. Healthy worker effect is proposed as an explanation of low atopy markers prevalence among PW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 31 publications
3
56
4
Order By: Relevance
“…This concentration range is comparable with those reported in other studies that have investigated ambient endotoxin concentrations in various countries (i.e., USA, Germany, Sweden, and Hong Kong) (Mueller-Anneling et al, 2004;Morgenstern et al, 2005;Tager et al, 2010;Nilsson et al, 2011;Cheng et al, 2012). However, the concentration range observed in the present study was lower than those reported in previous studies conducted in occupational settings, wherein the measurements were generally performed at the sources of endotoxins (Su et al, 2002;Madsen and Nielsen, 2010;Rimac et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…This concentration range is comparable with those reported in other studies that have investigated ambient endotoxin concentrations in various countries (i.e., USA, Germany, Sweden, and Hong Kong) (Mueller-Anneling et al, 2004;Morgenstern et al, 2005;Tager et al, 2010;Nilsson et al, 2011;Cheng et al, 2012). However, the concentration range observed in the present study was lower than those reported in previous studies conducted in occupational settings, wherein the measurements were generally performed at the sources of endotoxins (Su et al, 2002;Madsen and Nielsen, 2010;Rimac et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Various studies have demonstrated that exposure to high microbial contaminant concentrations results in respiratory disorders and decreased lung functions on various farms, including swine, grain, and poultry farms (Post et al, 1998;Kirychuk et al, 2003;Chattopadhyay et al, 2007;Chenard et al, 2007;Rimac et al, 2010;Szczyrek et al, 2011). However, scientific information on health risks to vegetable farm workers and the effect of their exposure to specific microbial agents, particularly fungi that are present on agricultural farms is scant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adverse effects of fungal exposure on farmers' lung functions are evident. In addition, susceptible workers might have left the industry due to the healthy worker effect and resulted in an underestimation of health impacts (Bunger et al, 2007;Chenard et al, 2007;Rimac et al, 2010). Second, we used a self-reported questionnaire to evaluate the working conditions and perceived health among the workers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In largescale poultry production, workers inside poultry barns and processing plants encounter high levels of ammonia, bacteria, and dust on the job. [5][6][7][8] Because of the high concentrations of the exposures and their irritant properties, bronchial hyperresponsiveness, 9 coughing, 9,10 wheezing, 10 nasal symptoms, 11,12 and changes in lung function 5,[8][9][10] have been investigated extensively among poultry barn workers. …”
mentioning
confidence: 99%